VD_FINDINFO Décision / 2016 / 252 vom 13. April 2016 - VD Tribunal cantonal (2016)
DÉTENTION PROVISOIRE, RISQUE DE RÉCIDIVE, RÉCUSATION, SOUPÇON | 221 al. 1 let. c CPP (CH), 227 CPP (CH), 393 al. 1 let. c CPP (CH), 56 CPP (CH)